THE SYRIAN CONFLICT DURING THE LEADERSHIP OF BASHAR AL ASHAD (International Conference on Social and Islamic Studies, 2022)
This article describes the figure of Bashar al Ashad who was the president of Syria for four terms. This study aims to explain the profile of the Bashar al Ashad figure, besides that the author also wants to explain the conflicts that occurred during Bashar al Ashad's leadership in the three periods (2000-2021). The results of the study explain that, Bashar al Ashad, whose background is a doctor, changed direction to become a military man and at the same time a politician who was sworn in as president of Syria since 2000 until now. Bashar al ashad is the next generation of the previous president as well as his biological father hafiz al ashad. During Bashar Al Ashad's leadership, Syria did not experience significant developments in the economic, social and political fields. However, what happened was armed conflict and chaos between the government and some Syrian people who opposed Bashar al Ashad's leadership.